Hydrological Assessment and Irrigation Water Optimization Based on Cropping Patterns in the Way Bungur Irrigation Area, Indonesia - Restika Putri; Frida Yassar Maula; Muhammad Rizki Arif; Ikhsan Maulidi; Vina Apriliani (International Journal of Hydrological and Environmental for Sustainability, 2025)
Efficient water management is essential for sustaining agricultural productivity, particularly in regions supported by technical irrigation systems such as the Way Bungur Irrigation Area in Pringsewu Regency, Indonesia. Although water availability in this region is generally adequate, its utilization remains inefficient due to cropping schedules that are not aligned with seasonal hydrological conditions, especially during the dry season. This study evaluates irrigation water requirements based on crop types and the official Cropping Pattern Plan (SK RTT), and compares them with water availability estimated using the F.J. Mock hydrological model. Input data include rainfall records, climatological parameters, river discharge, and field measurements. Crop water requirements were calculated using the FAO Penman–Monteith method, while water availability was assessed through dependable flow analysis. Results indicate that water availability in the Way Bungur watershed generally exceeds irrigation demand across three cropping seasons. However, temporal mismatches between planting schedules and water surplus or deficit periods lead to suboptimal water use. These findings highlight the importance of integrating annual water balance analysis into cropping pattern planning to enhance allocation efficiency, reduce risk, and promote sustainable agricultural development.